2013
DOI: 10.1159/000354305
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Problems in Children and Adolescents Who Have Disabilities

Abstract: The consequences of disability span almost all aspects of life, for families and for an affected individual. Endocrine aspects of disability cover disorders of hypothalamic pituitary dysfunction, bone health, puberty, fertility, sexual function and contraceptive needs. Adequate endocrine assessment for a child with a disability requires extensive and sensitive history to address social issues, general nutrition, vitamin D status, specific hypothalamic pituitary problems, together with parental concerns regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…CP is a complex condition that affects individuals differently. Its treatment and management are challenging because families, caregivers, and clinicians have to face, besides motor, cognitive, and neurologic disorders, also nutritional and respiratory concerns, infections, osteoporosis, and more rare endocrine problems [ 9 ]. Data from Worley et al described the physiological pattern of pubertal development observed in 207 CP children with moderate to severe motor impairment: girls seemed to enter puberty earlier but tended to mature over a longer period of time, menstruating later; boys followed more regular patterns but tended to start earlier [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…CP is a complex condition that affects individuals differently. Its treatment and management are challenging because families, caregivers, and clinicians have to face, besides motor, cognitive, and neurologic disorders, also nutritional and respiratory concerns, infections, osteoporosis, and more rare endocrine problems [ 9 ]. Data from Worley et al described the physiological pattern of pubertal development observed in 207 CP children with moderate to severe motor impairment: girls seemed to enter puberty earlier but tended to mature over a longer period of time, menstruating later; boys followed more regular patterns but tended to start earlier [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…It remains possible that, in children with developmental delay, precocious puberty might occur as an indirect result of the gene mutation and derive from disease-associated hypothalamic dysfunction, which could occur even without causative structural brain abnormalities. 28 Because the RAS-MAPK pathway is 1 of the intracellular signaling e2 pathways involved in growth hormone action, 29 -31 it is perhaps not surprising that growth hormone deficiency (GHD) has been described in patients with RASopathies, 9,10,23 although as with precocious puberty the exact etiology of this association is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…In girls who wear a harness in a wheelchair, breast development in puberty can cause discomfort due to chest tenderness with the harness impinging on the developing breast tissue. 15 If the girl is unable to express the pain, this might not be recognised by families and may just manifest as irritability.…”
Section: Discussionmentioning
confidence: 99%